2022
DOI: 10.1007/s11033-022-07230-6
|View full text |Cite
|
Sign up to set email alerts
|

Resolution-promoting autacoids demonstrate promising cardioprotective effects against heart diseases

Abstract: Chronic heart diseases have in common an unresolved inflammatory status. In atherosclerosis, myocarditis, myocardial infarction, or atrial fibrillation, mounting evidence suggests that unresolved inflammation contributes to the chronicity, aggravation, and morbidity of the disease. Following cardiac injury or infection, acute inflammation is a normal and required process to repair damaged tissues or eliminate pathogens and promote restoration of normal functions and structures. However, if acute inflammation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…MaR1 was also found to inhibit acute lung-injury-induced neutrophil infiltration and adhesion in mice and downregulate the generation of inflammatory mediators [ 18 ]. Studies have demonstrated that MaR1 is effective in preventing atherosclerosis and could be used as a new potential therapeutic strategy to eliminate arterial inflammation [ 19 ]. Nevertheless, the role of MaR1 in septic rats and its regulation on microglia in septic rats remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…MaR1 was also found to inhibit acute lung-injury-induced neutrophil infiltration and adhesion in mice and downregulate the generation of inflammatory mediators [ 18 ]. Studies have demonstrated that MaR1 is effective in preventing atherosclerosis and could be used as a new potential therapeutic strategy to eliminate arterial inflammation [ 19 ]. Nevertheless, the role of MaR1 in septic rats and its regulation on microglia in septic rats remains to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…If untreated and unresolved, the inflammatory status may lead to cardiomyocytes-, fibroblasts- and pro-inflammatory-(M1)-macrophage-induced production of inflammation-related compounds such as IL-6, TNFα, or NF-kB [ 121 , 122 , 123 , 124 ]. In the heart, such inflammatory signaling coupled with evident poisoning-induced oxidative stress has been demonstrated to promote abnormal calcium-Ca 2+ -handling, RyR2 dysfunction, delayed or shortened repolarization, triggered action potential, shortened effective refractory periods, and atrial fibrosis [ 15 , 109 , 125 , 126 ].…”
Section: Proposed Mechanisms Underlying the Association Between Pesti...mentioning
confidence: 99%